At Westonci.ca, we provide clear, reliable answers to all your questions. Join our vibrant community and get the solutions you need. Get quick and reliable solutions to your questions from knowledgeable professionals on our comprehensive Q&A platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
Let's solve the equation step-by-step carefully to identify the error Malik made.
Given the equation:
[tex]\[ \frac{2}{5} x - 4 y = 10 \][/tex]
We are also given that [tex]\( x = 60 \)[/tex], so substitute [tex]\( x = 60 \)[/tex] into the equation:
[tex]\[ \frac{2}{5} (60) - 4 y = 10 \][/tex]
Let's compute [tex]\(\frac{2}{5} (60)\)[/tex]:
[tex]\[ \frac{2}{5} \times 60 = \frac{120}{5} = 24 \][/tex]
Thus, the equation now becomes:
[tex]\[ 24 - 4 y = 10 \][/tex]
Next, isolate [tex]\( y \)[/tex] by subtracting 24 from both sides of the equation:
[tex]\[ -4 y = 10 - 24 \][/tex]
Simplify the right-hand side:
[tex]\[ -4 y = -14 \][/tex]
Now, solve for [tex]\( y \)[/tex] by dividing both sides by -4:
[tex]\[ y = \frac{-14}{-4} = 3.5 \][/tex]
Thus, the correct value of [tex]\( y \)[/tex] when [tex]\( x = 60 \)[/tex] is [tex]\( y = 3.5 \)[/tex].
Upon reviewing Malik's solution, he substituted [tex]\( y \)[/tex] with 60 in the second step, which was incorrect. The equation should have been solved for [tex]\( y \)[/tex] after substituting [tex]\( x \)[/tex], not after substituting [tex]\( y \)[/tex].
Therefore, the first error Malik made was in the second step:
[tex]\[ \frac{2}{5} x - 4(60) = 10 \][/tex]
This substitution of [tex]\( y = 60 \)[/tex] was incorrect.
Hence, the correct answer is:
Malik added 240 to each side of the equation.
Given the equation:
[tex]\[ \frac{2}{5} x - 4 y = 10 \][/tex]
We are also given that [tex]\( x = 60 \)[/tex], so substitute [tex]\( x = 60 \)[/tex] into the equation:
[tex]\[ \frac{2}{5} (60) - 4 y = 10 \][/tex]
Let's compute [tex]\(\frac{2}{5} (60)\)[/tex]:
[tex]\[ \frac{2}{5} \times 60 = \frac{120}{5} = 24 \][/tex]
Thus, the equation now becomes:
[tex]\[ 24 - 4 y = 10 \][/tex]
Next, isolate [tex]\( y \)[/tex] by subtracting 24 from both sides of the equation:
[tex]\[ -4 y = 10 - 24 \][/tex]
Simplify the right-hand side:
[tex]\[ -4 y = -14 \][/tex]
Now, solve for [tex]\( y \)[/tex] by dividing both sides by -4:
[tex]\[ y = \frac{-14}{-4} = 3.5 \][/tex]
Thus, the correct value of [tex]\( y \)[/tex] when [tex]\( x = 60 \)[/tex] is [tex]\( y = 3.5 \)[/tex].
Upon reviewing Malik's solution, he substituted [tex]\( y \)[/tex] with 60 in the second step, which was incorrect. The equation should have been solved for [tex]\( y \)[/tex] after substituting [tex]\( x \)[/tex], not after substituting [tex]\( y \)[/tex].
Therefore, the first error Malik made was in the second step:
[tex]\[ \frac{2}{5} x - 4(60) = 10 \][/tex]
This substitution of [tex]\( y = 60 \)[/tex] was incorrect.
Hence, the correct answer is:
Malik added 240 to each side of the equation.
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.